Systems and Constraints - Nicolas, Jean‐Marie (Remote Sensing Imagery, 2014)
A remote sensing satellite placed in orbit around the Earth is subject to several gravitational forces that will define its trajectory and motion. Orbit formalism dates as far as Kepler (1609), and the motion of satellites is modeled using Newton's laws. The Earth has specific properties; these specificities introduce several changes to the Kepler model: quite strangely, the consequences turn out be extremely beneficial for remote sensing satellites, since they allow us to have heliosynchronous sensors. This chapter analyzes orbital characteristics in order to draw some conclusions regarding the characteristics of imaging systems that orbit the Earth in quasi‐circular orbits. It provides the basis for the essential concepts in satellite imagery, which are perspective ray, resolution and ground swath. The chapter also gives an introduction on the notion of spectral resolution. The difficulty of implementing sensors is not the same in all areas of the electromagnetic spectrum.